PENGARUH SOCIAL MEDIA MARKETING, BRAND IMAGE dan e-WOM TERHADAP MINAT BELI KONSUMEN - Saputra, I Kadek Leon; Wardana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p05, 2023)
Social media marketing is a marketing communication activity that uses electronic media (online) to attract consumers in various forms to increase awareness, corporate image, and to increase sales. The presence of social media marketing makes information can be disseminated easily and cheaply. Therefore, at this time the company should be able to package information as attractively as possible through its social media to increase consumer buying interest. The purpose of this study is to explain the role of social media marketing as well as brand image and e-WOM in influencing consumer buying interest. This research was conducted at Trihita Vegan Restaurant. The sample taken was 100 respondents through purposive sampling method by distributing questionnaires in the form of google form with predetermined criteria. Measured by 15 indicators and using a Likert scale. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that all hypotheses are accepted. Social media marketing has a positive and significant effect on consumer buying interest. Brand image has a positive and significant effect on consumer buying interest. e-WOM has a positive and significant effect on consumer buying interest